Preventive measures for cross site request forgery attacks on Web-based Applications - Semastin E.; Azam S.; Shanmugam B.; Kannoorpatti K.; Jonokman M.; Samy G.N.; Sundresan Perumal (Science Publishing Corporation Inc, 2024)
Indexed by Scopus/ERA